ARE THE s-CEPHEIDS CROSSING THE INSTABILITY STRIP FOR THE FIRST TIME? - Andrievsky, S. M.; Garbuzov, G. A.; Doi, D. N. (Одеські астрономічні публікації, 2012)
Using the literature data on secular period changes reported for the small-amplitude Cepheids (s-Cepheids) it is shown that these stars are not crossing the instability strip for the first time. After correction of the observed pulsational chracteristics of s-Cepheids, in the diagram "log ( dP / P)100- log P" they become indistinguishable from usual classic Cepheids, which are supposed to have already crossed the instability strip more than (or at least) once.